(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Evaluating the effectiveness of antiseptic agents during the rehabilitation period after mandibular fractures in children is of great importance in clinical practice. Due to the high risk of wound surface infection, the proper selection and monitoring of antiseptics directly affect the speed of rehabilitation and the likelihood of complications. In recent years, digital technologies have been widely used for monitoring wound conditions, analyzing the dynamics of tissue healing, and assessing the effectiveness of antiseptic application. This study investigated the clinical impact of antiseptic agents in the treatment process following mandibular fractures in children using digital diagnostic methods. Mobile applications, digital image analysis, and remote monitoring technologies were employed to evaluate tissue regeneration stages, changes in inflammatory signs, and the correctness of antiseptic selection. The results demonstrated that digital technologies provide accurate and rapid monitoring of antiseptic effectiveness, contributing to improved rehabilitation quality. The findings hold significant scientific and practical value in introducing innovative approaches to wound management in pediatric dentistry.